Investigating the effect of clicker use on problem-solving among adult learners: A cross-sectional survey - Haifa Fahad Bin Mubayrik (Universidad de Deusto, 2020)
Classroom response systems (clickers) have been found to engage and attract student attention and facilitate the practical application of key ideas to solve problems. This study was designed to investigate the effects of clicker use on problem-solving among adult learners. A self-administered questionnaire was distributed to 60 students after giving them actual case studies for problem-solving using PowerPoint slides. An equal number of participants were assigned to each of the control (n=30) and experimental groups (n=30). Although both groups engaged in the same problem-solving tasks, the experimental group used clickers as a learning tool in the classroom. Data were analyzed using frequency, means, exploratory factor analysis, the Friedman ranking test, and linear regression analysis. The study findings revealed overall positive responses toward using clickers in the classroom. They also suggested that clickers encouraged thinking and problem-solving. It is concluded that problem-solving learning in adult education appears to be more effective when accompanied by clicker use than through conventional teaching methods. Received: 26 September 2019 Accepted: 04 March 2020 Published online: 19 May 2020